2011
DOI: 10.1002/maco.201005775
|View full text |Cite
|
Sign up to set email alerts
|

Impedance spectroscopy: An efficient tool to determine the non‐steady‐state chloride diffusion coefficient in building materials

Abstract: One of the most important problems of reinforced steel concrete in marine environments is the corrosion of the reinforcing bars. Most of the times, this corrosion is a consequence of the local destruction of the passive layer formed on the surface of the embedded steel, due to the arrival of chlorides present in the environment. Many efforts have been made to determine the chloride diffusion coefficient in concrete structures, both using natural diffusion methods, and accelerated migration methods. This coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…Many studies (4,5) have demonstrated that, for optimum laboratory conditions, the use of active additions produces a substantial improvement in chloride ingress resistance. In the particular case of CEM III, their better behaviour against chloride ingress could be related to the possible formation of Friedel's salt, because this cement has a higher content of Al 2 O 3 from the slag.…”
Section: Migración Forzada De Clorurosmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies (4,5) have demonstrated that, for optimum laboratory conditions, the use of active additions produces a substantial improvement in chloride ingress resistance. In the particular case of CEM III, their better behaviour against chloride ingress could be related to the possible formation of Friedel's salt, because this cement has a higher content of Al 2 O 3 from the slag.…”
Section: Migración Forzada De Clorurosmentioning
confidence: 99%
“…Many studies (1,3,4) have shown that, exposed to optimum laboratory conditions, the cements which incorporate these additions present a good behaviour with regard to service properties, even better than that observed for Portland cement (5,6). Blast-furnace slag has hydraulic properties, therefore it would start to react since the setting moment, while fly ash has pozzolanic properties, so their particles need the presence of portlandite, produced during clinker hydration, for starting to react (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…McCarter et al (2000) reported that the electrical conductivity and permeability and the diffusion coefficient of mortar showed a good correlation, which shows the relationship between the electrical conductivity and other properties of cement-based materials. In addition, there have been many studies investigating the correlation between the electrical conductivity and other properties of concrete (Andrade 1993;Streicher and Alexander 1995;Sánchez et al 2011;Ortega et al 2012;Shi et al 1999;Díaz et al 2006;Mercado et al 2012;Buenfeld and Newman 1987;Shane et al 2000;Vedalakshmi et al 2008;Neithalath and Jain 2010;Minagawa et al 2010). However, most studies have investigated limited ranges of water to cement ratios (W/C 0.4-0.6), and the relationship between the porosity and conductivity of mortar or concrete, which includes the effect of the interfacial transition zone (ITZ), was established as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Most techniques rely still today on saturated samples [1,[4][5][6][7][8][9][10][11]. Yet, in-situ structures are hardly encountered in saturated state.…”
Section: Introductionmentioning
confidence: 99%